2016
DOI: 10.1098/rspa.2016.0638
|View full text |Cite
|
Sign up to set email alerts
|

Lamb's problem on random mass density fields with fractal and Hurst effects

Abstract: Lamb's problem on random mass density fields with fractal and Hurst effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…To what extent is the average solution for a heterogeneous random medium different from the classical solution for a homogeneous medium? While various stochastic models have been developed to incorporate the spatial random fluctuations in wave propagation studies, the present paper continues the recent research line [9] aimed at grasping the fractal and Hurst characteristics of typically observed natural patterns [7] in transient wave propagation. Such effects are represented in Cauchy and Dagum random fields (RFs) [3,13], which have been developed over the past two decades.…”
Section: Introduction the Basic Question In Stochastic Wave Propagatmentioning
confidence: 98%
See 4 more Smart Citations
“…To what extent is the average solution for a heterogeneous random medium different from the classical solution for a homogeneous medium? While various stochastic models have been developed to incorporate the spatial random fluctuations in wave propagation studies, the present paper continues the recent research line [9] aimed at grasping the fractal and Hurst characteristics of typically observed natural patterns [7] in transient wave propagation. Such effects are represented in Cauchy and Dagum random fields (RFs) [3,13], which have been developed over the past two decades.…”
Section: Introduction the Basic Question In Stochastic Wave Propagatmentioning
confidence: 98%
“…Such effects are represented in Cauchy and Dagum random fields (RFs) [3,13], which have been developed over the past two decades. In particular, whereas [9] was focused on the in-plane Lamb's problem, this paper studies its anti-plane version, which deals with a transient out-of-plane load applied at the free surface of half-space. The resulting wave motion is pure shear, horizontally polarized, also called SH wave.…”
Section: Introduction the Basic Question In Stochastic Wave Propagatmentioning
confidence: 99%
See 3 more Smart Citations